Perceived Racial Discrimination and the Health of Black Youth in Ohio - Kenneth J. Steinman; Townsand Price-Spratlen; Christopher Browning (Ohio Journal of Public Health, 2020)
Background: Perceived racial discrimination (PRD) is known to harm youth, yet few studies use large, representative samples or study caregivers' perceptions of their children's experiences with unjust treatment. We examined how such a measure of PRD was associated with demographic characteristics as well as with physical and mental health outcomes for Black youth across Ohio. Methods: The 2019 Ohio Medicaid Assessment Survey was a complex telephone survey with a representative sample of 31 558 adults, 907 of whom completed a proxy interview for a youth in the household who was Black and age 6 to 18 years. One item from an Adverse Childhood Experiences (ACEs) scale assessed PRD: "To the best of your knowledge, has [name] ever experienced any of the following? Treated or judged unfairly because of [her/his] race or ethnic group." Results: Weighted analyses found that PRD was more common among Black youth who were older, from higher income families, and lived in rural counties. Perceived racial discrimination was also associated with frequent mental distress and with having an emotional or behavioral problem that needs treatment or counseling. It was not associated with any physical health outcomes measured. Conclusion: Our findings resemble those from other studies that use more extensive measures of PRD. While no substitute for extensive measures, the ACEs single-item measure may expand opportunities to study PRD in subgroup analyses of larger, representative samples. Yet our findings and those from other studies already provide considerable evidence that efforts to improve Black youth's mental health should consider their experience with PRD.
Keywords: Racial discrimination; Health outcomes; Child; Adolescent; African American